A THREE-YEAR AUDIT OF RIGID OESOPHAGOSCOPY AT LADY READING HOSPITAL PESHAWAR - Nadeem, Asif; Bilal, Aamir; Afridi, Kamal; ullah, Muqeet (Journal of Ayub Medical College Abbottabad, 2006)
Background: The number of oesophagoscopies performed annually provides an indication of the extent of oesophageal disorders in any particular setting. The present study aimed to provide such data for rigid oesophagoscopy at the only referral centre for this procedure in Peshawar. Methodology: An audit of all available records of patients undergoing rigid oesophagoscopies from January 2002 to December 2004, at the Lady Reading Hospital Peshawar was performed. Results: A total of 200 cases of rigid oesophagoscopies were performed during this three-year period of study. The ages of patients ranged from 1 to 90 years, with a two fold male preponderance. The main indication was dysphagia, with major causes being oesophageal carcinoma (115, 57.5%), reflux oesophagitis (56, 28%), strictures of various aetiologies (19, 9.5%) and foreign bodies (10, 5%). Successful dilatation was possible in 70% of cases; the morbidity rate was 4.5% due to perforation observed in 9 cases. The mortality rate was 1.5% due to septicemia in 3 cases. Conclusion: A high rate of rigid oesophagoscopies was observed indicating an increased frequency of oesophageal disorders in this setting. The morbidity and mortality rates observed are within acceptable ranges for this procedure. Key Words: Dysphagia, Oesophageal Carcinoma, Peptic Stricture, Oesophageal Perforation, Oesophagoscopy